Media framing on Muslims and Islam in Christchurch mosque attack : a content analysis of The Press and New York Times online news - Lim, Lai Hoon (Penerbit Universiti Kebangsaan Malaysia, 2021)
For decades, and particularly since September 11 attacks, media framing of Muslims as terrorists was persistent. Considerable studies showed that Western media framed Islam and Muslims as the major terrorism posing threat to Western society. Islam is depicted as a monolithic and homogenized religion whereas Muslims are uncivilized and inhuman religious maniacs. News coverage on terrorism, which involved Muslims as the perpetrator, heightened the fear culture for Muslims and Islam, eventuate the rise of “Islamophobia”. The media portrayed perpetrators of Muslims as terrorists who clashed the Western civilization and threatened public security as a whole. However, the recent Christchurch mosque attack that happened on 15 March 2019 in New Zealand, killed more than 50 Muslims by a local extremist, turned Muslims into terrorism victims. Despite abundant studies criticising Islamophobic representations of Muslims in Western media, there is scant literature examining the coverage of terrorism act where perpetrators are non-Muslims and victims are Muslims. Therefore, it is interesting to scrutinize how Islam and Muslims were framed in two influential online news sites, The Press and New York Times, where Muslims appeared to be the victims of the attack. By using framing analysis as the theoretical framework, this study examined the news themes covered in portraying Muslim victims and Islam for the incident. The finding determined how media framing of Muslim victims and Islam in the Christchurch mosque attack transformed the media event into international mourning in a climate of counter-Islamophobia.